The radial intercepts method for measuring bronchial mucous gland volume. - Alli, A F (1975)
A new linear method, the radial intercepts method, has been introduced for quantitating the components of the bronchial wall. The method is an adaptation of Rosiwal's (1898) original linear measurement technique, but unlike Rosiwal's the radial intercepts method takes measurements along radii at regular sectoral intervals. The method is reproducible and, from its high correlation with the standard planimetric, cut-weigh, and point-count techniques for quantifying bronchial wall components (Bedrossian, Anderson and Foraker, 1971), it is concluded that the method is reliable.